Pengaruh Metode Fermentasi Terhadap Kadar Protein pada Ikan Kembung (Rastrelliger sp) - Abdul Rohman Nasrudin; Samsidar; Luchiandini Ika Pamaharyani; Ricko Firdaus Rijaluddin Ahmad (Faculty of Science and Technology University Ibrahimy, 2026)
Peda is a traditional fermented fish product widely consumed in Indonesia and has potential as a protein source. Different fermentation methods are thought to affect the nutritional quality of the product, particularly its protein content. This study aims to determine the effect of fermentation methods on the protein content of mackerel peda (Rastrelliger sp.). The study was conducted using an experimental method with a completely randomized design (CRD) consisting of four treatments, namely fish cleaned until stage I fermentation, fish cleaned until stage II fermentation, fish not cleaned until stage I fermentation, and fish not cleaned until stage II fermentation, each with three replicates. Protein content analysis was performed using the Kjeldahl method, while data were statistically analyzed using analysis of variance and follow-up tests. The results showed that the fermentation method significantly affected the protein content of mackerel peda. The treatment of fish that were cleaned until fermentation stage I produced the highest protein content, while the treatment of fish that were not cleaned until fermentation stage II produced the lowest protein content. In general, stage II fermentation and the use of unscaled fish resulted in a decrease in protein content. The results of this study indicate that control of the fermentation method, particularly the fermentation stage and raw material treatment, is important for maintaining the nutritional quality of mackerel peda.